MAKING SENSE OF EARLY GAUḌĪYA VAIṢṆAVA MYSTICAL THEOLOGY: A MULTIDISCIPLINARY APPROACH TO THE STUDY OF HISTORY AND MYSTICISM. - Chilcott, Travis (Philosophy East & West: A Quarterly of Comparative Philosophy, 2025)
The article focuses on understanding early Gauḍīya Vaiṣṇava mystical theology through a multidisciplinary lens, particularly analyzing the work of Jīva Gosvāmin and his theory of mystical pluralism. Topics include the classification of divine experiences into three types (brahman, paramātman, bhagavān), the influence of soteriological practices on mystical perception, and parallels between Jīva's theology and modern constructivist models of mysticism.